CRISPR/Cas12a-Enhanced Loop-Mediated Isothermal Amplification for the Visual Detection of Shigella flexneri - Shi, Yaoqiang; Kang, Lan; Mu, Rongrong; Xu, Min; Duan, Xiaoqiong; Li, Yujia; Yang, Chunhui; Ding, Jia-Wei; Wang, Qinghua; Li, Shilin (Frontiers in Bioengineering and Biotechnology, 2022)
Shigella flexneri is a serious threat to global public health and a rapid detection method is urgently needed. CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated) system is widely used in gene editing, gene therapy, and in vitro diagnosis. Here, we combined loop-mediated isothermal amplification (LAMP) and CRISPR/Cas12a to develop a novel diagnostic test (CRISPR/Cas12a-E-LAMP) for the diagnosis of Shigella flexneri. The CRISPR/Cas12a-E-LAMP protocol conducts LAMP reaction for S. flexneri templates followed by CRISPR/Cas12a detection of predefined target sequences. LAMP primers and sgRNAs were designed to the highly conserved gene hypothetical protein (Accession: AE014073, Region: 4170556-4171068) of S. flexneri. After the LAMP reaction at 60 °C for 20 min, the pre-loaded CRISPR/Cas12a regents were mixed with the LAMP products in one-tube at 37 °C for 20 min, and the final results can be viewed by naked eyes with a total time of 40 min. The sensitivity of CRISPR/Cas12a-E-LAMP to detect S. flexneri was 4*100 copies/μL plasmids, and without cross-reaction with other 6 closely related non-S. flexneri. Therefore, the CRISPR/Cas12a-E-LAMP assay is a useful method for the reliable and quick diagnosis of S. flexneri and may be applied in other pathogens infection detection.